Peran Mahasiswa dalam Penguatan Literasi Membaca di SD Negeri 173320 Siborutorop melalui Program Kampus Mengajar Angkatan 3 - Maria Helmi Lumban Gaol; Monalisa Marta Siahaan; Rince Rince; Yen Aryini; Renta Hutasoit (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The teaching campus is one of the independent campus programs designed by the Ministry of Education, Culture, Research, and Technology. In practice, this program provides a mandate to students to be able to carry out learning to students that focuses on understanding literacy and numeracy. The main purpose of the campus teaching program is to provide opportunities for students to learn and develop themselves through activities outside of class lectures, to help schools provide optimal educational services for all students at the elementary level in limited and critical conditions during the pandemic and to provide optimal learning opportunities. to all students at the elementary level in limited and critical conditions during the pandemic. The special purpose of the class III teaching campus program in 2022 is that with the program design that we offer for SD Negeri 173320 Siborutorop, I can succeed in the independent campus program organized by the Ministry of Education and Culture, students have made real contributions as evidence of students also caring and play an active role in the success of the Kemendikbud program for the advancement of national education and make Indonesian students trained to serve, especially in the field of education, through this program students from all majors are free to serve, contribute and collaborate with teachers creatively and innovatively to advance literacy and numeracy in elementary schools State 173320 Siborutorop. The activities carried out while at SD Negeri 173320 Siborutorop were teaching activities, and helping teachers in strengthening reading literacy in schools.